DEVELOPMENT OF OCCUPATIONAL STANDARDS USING THE INSTRUMENTS OF PUBLIC-PRIVATE PARTNERSHIP - Radkevych, Valentyna; Borodiyenko, Oleksandra; Kolyshko, Rodion; Korotkova, Lina (Professional Pedagogics, 2020)
Relevance: the post-industrial stage of society’s development makes it necessary to modernize the vocational education system, the important direction of which is to update the existing approaches to the development of occupational standards in Ukraine. These are documents which approve the requirements for the competencies of workers in the prescribed manner and which should be focused on modern social and economic relations and consider the change in the technological structure that will require a high level of vocational competency of skilled workers for all economic sectors, as well as improving the system of training and advanced training. All this makes it more relevant to involve partners within the framework of of Public-Private Partnership (PPP) in the process of ... Purpose: to substantiate modern approaches to the development of occupational standards using the instruments of Public-Private Partnership. Methods: analysis of scientific literature and legal documents - to determine current trends in the development of occupational standards and current status of the process; methods of analysis and synthesis - to classify job functions and occupational standards, systematize data, summarize management experience to develop theoretical and methodological approaches to determining the conditions for the development of occupational standards; comparative analysis, synthesis and expert evaluation methods - to develop requirements for the development of occupational standards. Results: the structure of current vocational qualifications system is revealed, its features in the context of modern labor market orientation and increase in the level of employment are specified, the conditions and prospective of occupational standards development are determined. Conclusions: the structure of occupational standards and conditions for their development with a focus on specific job functions for certain spheres of economic activity using the instruments of Public-Private Partnership are determined, which is an important basis for obtaining competencies according to criteria of efficiency and labor market demands.